(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the significance of differential X-ray diagnostics in the evaluation of respiratory diseases. The rapid development of modern radiology has made X-ray imaging one of the most widely used and cost-effective diagnostic tools in pulmonary medicine. The article provides an overview of the radiological features of common respiratory disorders such as pneumonia, tuberculosis, lung cancer, chronic obstructive pulmonary disease (COPD), and interstitial lung diseases, and discusses the principles of differential diagnosis through X-ray examination.